Pengalaman Komunikasi Terapeutik Perawat Orang Lanjut Usia - Antar Venus; Dina Nabilah (Postgraduate of Jayabaya University, 2016)
Although some research related to the influence of therapeutic communication to patients has been carried out in Indonesia, research trying to explore the experience of the elderly nurse communication has never been done. Though the geriatric is a practitioner who has interacted daily with elderly patients thus have therapeutic communication experience that deserves to be explored. By using phenomenology, the study describe the experience of five geriatric nurse in conducting therapeutic communication activities for elderly patients in Sasana Tresna Werdha Jakarta. Data was collected through interviews. The informants of this research are interviewed about 45-90 minutes. In the interview the informant’s provide their personal experience that contribute to the success of their therapeutic communication. Based on this study, we found ten important themes in therapeutic communicate with elderly patients, namely: the planned communication, to find out, observation, appreciation and humor, taboo communication, respect, caring, clarity, empathy and build rapport. The ten themes above we made to three (3) things that become the main learning and the essence in this study. 3 (three) it was planned, caring, and empathy are the answer to the research question.